Gaultheria (Ericaceae) of Myanmar: an updated species list for the country, a new species, and a new species combination - Fritsch, Peter W.; Armstrong, Kate E.; Aung, Mu Mu; Fujikawa, Kazumi; Lu, Lu (Phytotaxa, 2023)
An updated list of the species of Gaultheria (Ericaceae) from Myanmar is presented, with additions and corrections to a previously published list. Gaultheria natmataungensis, a new species from Natma Taung National Park, Chin State, Myanmar, is described and illustrated. It is the only species of Gaultheria endemic to the country. Additionally, G. griffithiana var. insignis is raised to the rank of species (G. insignis), and G. insignis and G. suborbicularis are newly recorded for Myanmar. Photographs of living plants of G. insignis are included, along with an updated description and illustration that incorporate new morphological data, including the first documentation of floral characters. Lectotypes are provided for G. fragrantissima, G. insignis, and G. nummularioides. A key to the species is provided. The number of Gaultheria species recorded from Myanmar is 24.